Licensing Effect in Consumer Choice - Khan, Uzma; Dhar, Ravi (Journal of Marketing Research, 2006)
Most choices in the real world follow other choices or judgments. The authors show that a prior choice, which activates and boosts a positive self-concept, subsequently licenses the choice of a more self-indulgent option. The authors propose that licensing can operate by committing to a virtuous act in a preceding choice, which reduces negative self-attributions associated with the purchase of relative luxuries. Five studies demonstrate the proposed licensing effect of a prior commitment to a virtuous act on subsequent choice. Consistent with the authors' theory, the preference for an indulgent option diminishes if the licensing task is attributed to an external motivation. The authors also report a mediation analysis in support of their theoretical explanation that the licensing effect operates by providing a temporary boost in the relevant self-concept.